Evaluasi Desain Pengalaman Pengguna (UX) untuk Meningkatkan Interaksi di Lingkungan Metaverse - Muhammad Agha Afkar; Alesha Khaira (Yayasan Pendidikan Mitra Mandiri Aceh (YPMMA), 2024)
This study evaluates the role of User Experience (UX) design in enhancing user interaction within the Metaverse, a rapidly evolving virtual environment. The research highlights the importance of creating immersive, intuitive, and secure virtual experiences that enable seamless interaction while safeguarding user privacy and mental health. Key factors in effective UX design include clear interface elements, responsive controls, and mechanisms for personal data management. Through a qualitative approach involving case studies and user interviews, this research explores successful UX implementations and identifies strategies for optimizing user engagement. Collaboration between academia and industry is emphasized to ensure the development of inclusive, accessible, and innovative virtual environments. The study also discusses challenges such as digital addiction and social isolation, providing guidelines for mitigating risks and improving user satisfaction within the Metaverse.